HUBUNGAN SYARIAT ISLAM DAN PENDIDIKAN ISLAM - Firdaus Firdaus (Fakultas Agama Islam Universitas Islam Makassar (UIM), 2018)
Islamic Syari'ah has provided a new solution for the Islamic world with its various kinds. That is among the images of God's justice among His servants. In addition, Islamic education also aims to improve and guide morals in a more perfect direction, so the task of Islamic education is to direct educational processes and activities on the principles of Islamic teachings in accordance with the guidance of the Qur'an and the Hadith of the Prophet. Islamic education is very relevant to the Islamic Syari'ah with the achievement of the educational goals that we aspire together, namely the formation of a complete and perfect human person, so as to be able to feel the happiness and salvation of the life of the world and the hereafter. Between Islamic Syari'ah and Islamic education must be united and should not be separated from one another